Brine Shrimp Lethality Test Ekstrak Etanol Herba Pugun Tanoh (Picria fel terrae L.) - Tetty Noverita Khairani; Chemayanti Surbakti; Novika Sari Siregar (LPPM STIKes Indah Medan, 2021)
The Pugun Tanoh herbs (Picria fel terrae L.), a species of plant from the family Scrophulariceae. The study was to determine the percent mortality and LC50 value of the ethanolic extract of Pugun Tanoh herbs in Artemia Salina L. larvae by using the Brime Shirmp Lethality Test (BSLT). Treatment concentrations include 180.0 ppm; 200.0 ppm; 220.0 ppm; 240.0 ppm; 260.0 ppm; 280.0 ppm; and 300.0 ppm and 0.0 ppm as negative controls with three replications. Each concentration used 10 larvae of Artemia salina L. 48 hours old. Toxicity was identified based on percent larval mortality by probit analysis (LC50). The result is a linear equation, Y = 11.222X+65,427. The LC50 value was reached when the concentration was 188.691 ppm. Toxicity of the ethanolic extract of Pugun Tanoh herbs was tested by BSLT. It showed toxic properties, there was potential as an anticancer because LC50 < 1000.0 ppm.